2020
DOI: 10.18632/oncotarget.27478
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostudies on CNGRC-CPG2 fusion proteins for ligand-directed enzyme prodrug therapy for targeted cancer therapy

Abstract: The sequence asparagine-glycine arginine (NGR), flanked by Cysteine (Cys) residues so as to form a disulfide-bridge (CNGRC), has previously been found to target and bind specifically to aminopeptidase N (APN), which is highly expressed on the surface of tumor cells. The goal of this study was to develop and evaluate the potential of fusion proteins carrying the CNGRC sequence linked to the enzyme carboxypeptidase G2 (CPG2) for targeted cancer therapy. We refer to this strategy as ligand-directed enzyme prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The single and double CPG2–CNGRC fusion proteins produced showed “biobetter” features in binding specificity, stability and in vitro cytotoxicity. 18 Several PEGylation strategies have been established to improve the therapeutic potency of proteins/drugs through enhancing their stability and lowering immunotoxicity. 21 To enhance the therapeutic efficacy and to reduce the protein immunogenicity of the produced fusion proteins here we conjugated the previously generated CNGRC–CPG2 fusion proteins with PEG polymer and studied the effect of PEGylation on the anti-cancer targeting effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The single and double CPG2–CNGRC fusion proteins produced showed “biobetter” features in binding specificity, stability and in vitro cytotoxicity. 18 Several PEGylation strategies have been established to improve the therapeutic potency of proteins/drugs through enhancing their stability and lowering immunotoxicity. 21 To enhance the therapeutic efficacy and to reduce the protein immunogenicity of the produced fusion proteins here we conjugated the previously generated CNGRC–CPG2 fusion proteins with PEG polymer and studied the effect of PEGylation on the anti-cancer targeting effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Two different studies found that conjugation of CPG2 either with the fusion peptide (CNGRC) or PEG polymer formed fusion proteins and PEGylated CPG2, respectively with higher serum stability and lower ex vivo immunotoxicity compared with the nonfused or non-PEGylated CPG2. 10 , 18 In this study, we produced new PEGylated fused CPG2 proteins which tested for their stability and immunotoxicity. Our data showed that the serum stability of the PEGylated CPG2 fusion proteins was not changed in relation to the non-PEGylated ones ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that adding an extra cysteine residue to a cyclic nonapeptide, iRGD (CRGDK/RGPD/EC), improved the tumor penetrating function [33]. In addition, one cysteine residue may interact with cysteine(s) in other peptides to form peptide complexes [34]. It is also possible that the single cysteine residue in the original CooP sequence interacts with the cysteine residue (Cys 125 ) on the FABP3 sequence to stabilize the complex.…”
Section: Consequently Binding Affinity Measurements Performed By Micmentioning
confidence: 99%